Analisa Fundamental Makro, Fundamental Mikro, Terhadap Kinerja Keuangan dengan Struktur Kepemilikan, Struktur Modal dan Karakteristik Perusahaan Pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di BEI Tahun 2018-2023 - Fernianda Wahyu Ramadanthy; Hwihanus (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
The purpose of this research is to test the Macro Fundamentals and Micro Fundamentals on Financial Performance with Ownership Structure, Capital Structure, and Company Characteristics in the food and beverage Sector companies listed on the Indonesia Stock Exchange between 2018 and 2023. To test and analyze the population, consists of 30 food and beverage sector companies listed on the IDX. This research method uses random sampling with a sample size of five companies. The data analysis method in this study uses the Smart PLS (Partial Least Square) version 4 program. The research results indicate that out of the 13 hypotheses developed, 2 hypotheses are accepted, and 11 hypotheses are rejected.